Fenugreek: a plant-origin oral contraceptive product present and future - Allow, Ahmed Kaid Naji; Yehdih, Amer Abdy Mohamed (IIUM Press, International Islamic University Malaysia, 2017)
Anti-fertility agents have been used since long time to prevent pregnancy. Nowadays, Oral Contraceptive Pills are the most common and efficient tool despite their side effects. With the progress in therapeutic sciences, natural components from different herbs are likewise used. Trigonella foenum-graecum (fenugreek) is one of the used herbs. The purpose of the present book is to evaluate the anti-fertility effect of fenugreek seeds aqueous (FSA) extract “as a new plant origin contraceptive product that can be used as a supplement or oral medication in future. First we are going to show its effect on the female rats by assessing the reproductive hormones, relative ovarian weight as well as relative uterine weight, counting the ovarian follicles (secondary, Graafian, atretic follicles and corpora lutea) and measuring uterine endometrium thickness. This book is designed to cover newly discovered plant origin product which can be used as a contraceptive product. It is consists of seven chapters. In the first three chapters, we are going to give a good background about the fenugreek seeds and its utilization in the medicine in the past and present. Whereas in the fourth, fifth and sixth we are going to share our animal work experiences and evidences with its interpretation. In the last chapter, we are going to demonstrate our conclusions. The journey throughout the different angels of this book, which authors are planning to make readers get a good background about the anti-fertility treatment. The plant origin product that we are planning to get from this work will be the first plant-origin oral contraceptive product. Throughout the chapters, many of our research-works will be touched from different points to show our longstanding and promising experience and real outcomes. Finally, expert authors in the field of reproductive and alternative medicine prepared this work.